Perancangan Sistem Informasi Konsultasi Dokter Pada Lapas Narkotika Kelas IIB Muara Sabak - san toso; Gustinar; Saut Siagian (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2023)
Narcotics Correctional Institutions (Lapas) provide guidance, mental recovery, and behavior for narcotics users and dealers. Apart from that, prisons are also required to maintain the health of their inmates, as in the case study of this research at the narcotics prison class II B Muara Sabak. Health services that have been running so far are still conventional or manual, in which the inmates want to seek treatment and health checks through health workers (nurses) assigned to the prison, but in consultation services to doctors, nurses are always in contact via telephone or doctors can come directly. This is sometimes inconvenient, especially for busy doctors who can't immediately pick up the phone or who have the problem of telephone interference during consultations. For this reason, it is necessary to have a website-based consulting service system that needs to be designed to overcome this problem. The methods used in this research are problem analysis, material collection, system design, and prototypes. This research will produce a prototype of a health service information system and a doctor's consultation in which this system provides consultation services to doctors via chat via an online application system so that doctors can handle problems without having to come in person or via telephone. Consultation records and medical record history will always be stored in a database that makes it easier for officers to trace back, and health services for prison members can be handled quickly and effectively. Keywords : prison, consultation, doctor, online